Metabolomic profiling and micropropagation of Salvia africanalutea L. potent against Fusarium verticillioides - Nkomo, Mpumelelo (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.